Design and analysis of surface emitting distributed feedback laser for radio over fiber (ROF). (15th October 2008) - Witjaksono, Gunawan; Saraswati, Irma
This research is focused on design and analysis of semiconductor laser for ROF application. The alternative and advanced laser is designed for high performance operation and ease in manufacturing; that is a surface emitting distributed feedback (SEDFB) laser. Optimisation is performed at the wavelength of 1.55 µm using the horizontal-cavity structure. This device contains an active region by means of multi-quantum well (MQWs) structure and a separated confinement heterostructure (SCH) in order to optimise its performance. The simulation results in a ridge SEDFB structure producing a single-mode, 1550-nm output operation with optical confinement factor of 0.186, and far-field angle divergence of 450. The transverse edge loss is 0.031 cm−1. An optimum grating duty cycle is in the interval of 0.5-0.6, with a surface loss of 24cm−1. The resulting laser design has a single-lobe pattern with a differential quantum efficiency of 41.3%.